Spontaneous rupture of the renal pyelocaliceal system - M. E. Topuzov; T. H. Nazarov; S. M. Basok; A. G. Kanukoev; A. D. Kankasova (Вестник урологии, 2024)
Spontaneous rupture of the renal pyelocalyceal system (PCS) is a rare condition that can be challenging to diagnose. Unlike traumatic injuries, this condition is not easily identiﬁed based on clinical symptoms, anamnesis, or physical examination ﬁndings. However, in most cases, PCS rupture is a result of underlying medical conditions. Surgical intervention for ruptured PCS should aim to immediately drain the kidney and the retroperitoneal area. This report aims to illustrate a clinical case involving treatment of a patient with spontaneously ruptured PCS.